An Angler‐Friendly AI Pipeline for Self‐Reporting and Automatic Catch Analysis in Recreational Fisheries - Marco Signaroli; Bernat Morro; Eugenio Cutolo; Ignacio A. Catalán; Inmaculada Riera; Antoni Mira; Clara Mecinas; Antoni M. Grau; Yolanda Gonzalez‐Cid; Josep Alós (Fish and Fisheries, 2026)
Monitoring recreational fisheries is difficult: anglers are widely dispersed, gear and practices vary, and many species are involved, which leads to fragmented and scarce data. To address these issues, we developed an Artificial Intelligence (AI) pipeline that turns angler‐reported photos into standardised records of catch composition and individual body lengths. The workflow consists of four steps: (i) automatic fish detection, (ii) pixel‐accurate segmentation, (iii) species classification trained with few labelled images and (iv) length estimation calibrated with a measurement board carrying fiducial markers (machine‐readable reference tags). We validated the system on smartphone images from a mixed‐species fishery in the western Mediterranean under realistic conditions (variable lighting, occlusions, mixed catches). The detection–segmentation stage achieved F1≈0.93. The classifier reached 85% accuracy across 38 species using only 12 training images per species, showing strong data efficiency. Length estimates were robust, with centimetre‐level error suitable for size‐class analyses. Leveraging large, pre‐trained foundation models, only a lightweight adapter requires training, keeping data and compute demands low and enabling rapid extension across regions, gear types and species lists. When integrated with existing catch‐reporting smartphone applications and agency workflows, the pipeline delivers instant angler feedback and streams standardised, analysis‐ready records to managers. In practice, this unlocks operational monitoring: near‐real‐time indicators of catch composition and length structure, automated size‐limit compliance checks and cost‐efficient inputs to stock assessment and adaptive management.

Reliability of self-reported catch and effort data via a smartphone application in a multi-species recreational fishery - Bernat Morro; Inmaculada Riera-Batle; Antoni Mira; Clara Mecinas; Antoni M. Grau; Josep Alós (Fisheries Research, 2025)

Meta‐analysis approach to the effects of live prey on the growth of Octopus vulgaris paralarvae under culture conditions - Diego Garrido; M. Virginia Martín; Covadonga Rodríguez; José Iglesias; Juan C. Navarro; Alicia Estévez; Francisco Hontoria; Mikel Becerro; Juan J. Otero; Josu Pérez; Inmaculada Varó; Diana B. Reis; et al. (Reviews in Aquaculture, 2018)
The common octopus ( Octopus vulgaris , Cuvier 1797) is a promising species for aquaculture diversification, but the massive mortality during the first life stage is the main bottleneck for its commercial production. The aim of the present study was to compare the effects of different live preys ( Artemia and crustacean zoeae) and/or Artemia enrichment protocols in the paralarval growth by using a meta‐analysis approach. A total of 26 independent assays were used, including data from the bibliography and from experiments carried out by our group. Three comparisons were established: (i) crustacean zoeae vs. Artemia , (ii) different crustacean zoeae species and (iii) Artemia enriched with marine lecithin (rich in polar lipids‐ PL and docosahexaenoic acid‐ DHA ) vs. previously used Artemia enrichments. The meta‐analysis approach allowed a quantitative review of independent studies with reliable conclusions, avoiding the subjectivity inherent to classical reviews. The outputs provided statistical confirmation of the better suitability of crustacean zoeae with respect to Artemia . However, not all crustacean species showed the same results, given that the high variability on Grapsus zoeae hampered finding significant differences with respect to the control treatment ( Artemia ). Nutrient composition and biometry of the different types of prey are discussed as possible causes of the differences arising from the meta‐analysis. Finally, the present results suggest that marine lecithin has a beneficial effect on paralarval growth with respect to previously used enrichments, which could be related to the increase in DHA and PL in Artemia , given the essential role of these lipid components in octopus paralarval physiology.